Risk factors and management of obstetric fistula associated with bladder calculus at Saint Joseph Hospital, Kinshasa - DR Congo - Nembunzu, Dolores; Mpunga, Michel; Banze, Félicien; Tena, Brian Tena; Tripathi, Vandana (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: Obstetric fistula can be complicated by bladder calculus. The mechanism of lithogenesis is caused by some predisposing factors. The article aims to describe risk factors predisposing to bladder calculus formation and repair outcome. Methods: This was a comprehensive retrospective review from medical records of fistula obstetric repairs associated with bladder calculus at Saint Joseph Hospital in Kinshasa, DR Congo, from January 2007 to December 2017. Results: Among 1416 women who had had obstetric fistula, 30 (2.12%) had bladder calculus. The average age of women was 38 years old and ranged between 22 and 82 years old. The average duration of fistula was 8 years and ranged from 5 months to 31 years. All fistulas were iatrogenic and 86.67% (n = 26) occurred after caesarean section. Size of calculus varied between 1 cm and 15 cm. Risk factors identified were: urinary tract infection 80% (n = 24), foreign bodies 13.33% (n = 4), malnutrition and dehydration in 33.33%. In majority of cases (90%), the removal of the calculus and repair of fistula were performed at the same time by transvesical way. 70.37% of the patients had successful repairs. Conclusions: Iatrogenic fistula after caesarean section, urinary tract infection and foreign bodies are related to the formation of bladder calculi. Fistula repair and extraction of bladder calculus performed at the same time gives good results. Access to Obstetric Emergency Care, qualified personnel and available infrastructure and equipment are important for the prevention of the occurrence of bladder calculus.